Effect of Head Rotation on Cerebral Blood Velocity in the Prone Position - Jakob Højlund; Marie Sandmand; Morten Sonne; Teit Mantoni; Henrik L. Jørgensen; Bo Belhage; Johannes J. van Lieshout; Frank C. Pott (Anesthesiology Research and Practice)
Background. The prone position is applied to facilitate surgery of the back and to improve oxygenation in the respirator-treated patient. In particular, with positive pressure ventilation the prone position reduces venous return to the heart and in turn cardiac output (CO) with consequences for cerebral blood flow. We tested in healthy subjects the hypothesis that rotating the head in the prone position reduces cerebral blood flow. Methods. Mean arterial blood pressure (MAP), stroke volume (SV), and CO were determined, together with the middle cerebral artery mean blood velocity (MCA Vmean) and jugular vein diameters bilaterally in 22 healthy subjects in the prone position with the head centered, respectively, rotated sideways, with and without positive pressure breathing (10 cmH2O). Results. The prone position reduced SV (by 5.4±1.5%; P<0.05) and CO (by 2.3±1.9